UJI COBA PROSES KOAGULASI-FLOKULASI AIR BAKU UNTUK PDAM DANAU TELOKO DAN TELUK GELAM DI KAYU AGUNG KABUPATEN OKI PROPINSI SUMATERA SELATAN - Rahardjo, Petrus Nugro (Jurnal Air Indonesia, 2010)
Regional Drinking Water Company (PDAM) of County Ogan Komering Ilir has two problematic water treatment units. The first is located in Danau Teloko and the other is in the Teluk Gelam. The main problem is that many organic pollutants (namely peat water) contained in raw water. Therefore, PDAM can not be optimal to supply all the needs of drinking water for the community. PDAM have tried to treat the raw water of peat with the process of flocculation and coagulation, but the results did not meet quality standards as drinking water. This research is a trial test to obtain the optimum condition for flocculation and coagulation processes in water treatment. The results were very succesful and get the optimum pH is about 7.5 and a chemical dose of 80 ppm Aluminum Sulphate as the coagulant. Turbidity of water produced is 4 NTU and visually looks very clean. Better to add a synthetic polymer (PAC) as an additive to the process of flocculation and coagulation. Based on calculations, PDAM Danau Teloko will require the amount of coagulant (Aluminum Sulphate) 138.24 kg per day to produce 40 liters of drinking water per second. Keywords : Raw Water, Flocculation, Coagulation, Water Treatment Plant